Crystallized phenol treatment is less effective in patients with recurrent pilonidal disease after surgery compared to patients with primary pilonidal disease (Annals of Medical Research, 2021)
Aim: Primary pilonidal disease can be treated with crystallized phenol with an overall cure rate of 80%. However, the effect of crystallized phenol in patients who had recurrence after pilonidal disease surgery has not been analyzed in the English medical literature in detail yet. The purpose of this study was to investigate the effect of crystallized phenol in recurrent pilonidal disease. Material and Methods: 28 male and 10 female patients who had recurrence after surgical intervention to treat pilonidal disease were evaluated. Twenty male and 8 female patients underwent excision and primary closure surgery, whereas 8 male patients and 2 female patients underwent modified Limberg flap surgery. All of these 38 patients were treated with one-time application of crystallized phenol.Results: The mean period for recurrence of patients treated with single application of crystallized phenol after primary excision and primary closure surgery was 45.85±11.82 days (range: 35-90 days) and it was 66.5±25.31 days (range: 40-120 days) after modified Limberg flap surgery. The follow-up period was 6 months. The cure rate in recurrent excision and primary closure group was 57.14%, whereas the cure rate in the recurrent modified Limberg flap group was 40%. Overall cure rate was 52.63%.Conclusion: As a result, crystallized phenol treatment was less effective in patients who had recurrence after pilonidal disease surgery in comparison to patients who were only treated with crystallized phenol without prior surgical intervention.
Keywords: Crystallized phenol; pilonidal disease; recurrence